]> matita.cs.unibo.it Git - helm.git/blobdiff - helm/matita/library/demodulation_coq.ma
A few paramodulation/demodulation tests moved from library to tests.
[helm.git] / helm / matita / library / demodulation_coq.ma
diff --git a/helm/matita/library/demodulation_coq.ma b/helm/matita/library/demodulation_coq.ma
deleted file mode 100644 (file)
index aa9d5f1..0000000
+++ /dev/null
@@ -1,52 +0,0 @@
-(**************************************************************************)
-(*       ___                                                              *)
-(*      ||M||                                                             *)
-(*      ||A||       A project by Andrea Asperti                           *)
-(*      ||T||                                                             *)
-(*      ||I||       Developers:                                           *)
-(*      ||T||         The HELM team.                                      *)
-(*      ||A||         http://helm.cs.unibo.it                             *)
-(*      \   /                                                             *)
-(*       \ /        This file is distributed under the terms of the       *)
-(*        v         GNU General Public License Version 2                  *)
-(*                                                                        *)
-(**************************************************************************)
-
-set "baseuri" "cic:/matita/demodulation/".
-
-include "legacy/coq.ma".
-
-alias num = "natural number".
-alias symbol "times" = "Coq's natural times".
-alias symbol "plus" = "Coq's natural plus".
-alias symbol "eq" = "Coq's leibnitz's equality".
-alias id "nat" = "cic:/Coq/Init/Datatypes/nat.ind#xpointer(1/1)".
-alias id "S" = "cic:/Coq/Init/Datatypes/nat.ind#xpointer(1/1/2)".
-
-
-theorem p0 : \forall m:nat. m+O = m.
-intro. demodulate.
-
-theorem p: \forall m.1*m = m.
-intros.demodulate.reflexivity.
-qed.
-
-theorem p2: \forall x,y:nat.(S x)*y = (y+x*y).
-intros.demodulate.reflexivity.
-qed.
-
-theorem p1: \forall x,y:nat.(S ((S x)*y+x))=(S x)+(y*x+y).
-intros.demodulate.reflexivity.
-qed.
-
-theorem p3: \forall x,y:nat. (x+y)*(x+y) = x*x + 2*(x*y) + (y*y).
-intros.demodulate.reflexivity.
-qed.
-
-theorem p4: \forall x:nat. (x+1)*(x-1)=x*x - 1.
-intro.
-apply (nat_case x)
-[simplify.reflexivity
-|intro.demodulate.reflexivity]
-qed.
-